2019
DOI: 10.1159/000502698
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional Status Assessment in Children and Adolescents with Various Levels of Physical Activity in Aspect of Obesity

Abstract: <b><i>Introduction:</i></b> A rational way of nourishment, combined with adequate physical activity, are the basic components of maintaining proper body condition. <b><i>Objective:</i></b> The aim of the study was to evaluate nutritional status among children and adolescents with different levels of physical activity. <b><i>Methods:</i></b> The study group consisted of 1,013 students of both genders aged between 7 and 18 years attending el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 27 publications
1
12
1
2
Order By: Relevance
“…17 Jerzy et al reported 19.2% overweight and 7.4% obese subjects. 18 In our study, we found underweight children 64% & 60% of government and private respectively mainly while overweight children were 4% in government sector and no case was reported in private sector. The difference of the results may be due to change of geographic characteristics as well as other socio-economical factors.…”
Section: Graph 1: Comparison Of Weight Among Government and Private School Childrenmentioning
confidence: 43%
“…17 Jerzy et al reported 19.2% overweight and 7.4% obese subjects. 18 In our study, we found underweight children 64% & 60% of government and private respectively mainly while overweight children were 4% in government sector and no case was reported in private sector. The difference of the results may be due to change of geographic characteristics as well as other socio-economical factors.…”
Section: Graph 1: Comparison Of Weight Among Government and Private School Childrenmentioning
confidence: 43%
“…A study by [ 48 ] demonstrated that BMI is significantly associated with physical activity during puberty (13–18 years) in boys and in pre-pubertal girls aged 7–12 years [ 48 ]. A study by [ 49 ], however, found that there was no significant relationship between the type of class (i.e., general education vs. sports focused). in the incidence of overweight and obesity based on BMI [ 49 ], which is consistent with our results ( Table 2 ), where the most children fell within healthy weight BMI percentile ranges ( Table 3 ), but generally much weaker physical condition was observed in GC.…”
Section: Discussionmentioning
confidence: 99%
“…Gizi yang berkualitas sangat penting karena pada usia tersebut anak mengalami tumbuh kembang yang pesat (Sugiyanto, Sumarlan and Hadi, 2020). Selain itu anak usia sekolah dapat dijadikan media pembawa perubahan (agent ofchange) bagi pembentukan perilaku gizi bagi diri sendiri dan keluarganya (Słowik et al, 2019).…”
Section: Pendahuluanunclassified